2019
DOI: 10.1080/09712119.2019.1636800
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary Macleaya cordata extract on growth performance, immune responses, antioxidant capacity, and intestinal development in weaned piglets

Abstract: View related articles View Crossmark data Citing articles: 1 View citing articles Effects of dietary Macleaya cordata extract on growth performance, immune responses, antioxidant capacity, and intestinal development in weaned piglets

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 65 publications
2
25
0
Order By: Relevance
“…In order to assess the antioxidant capacity of MCE, several antioxidant parameters such as T-AOC, SOD, GSH-Px, and MDA in serum were monitored. It has been reported that the T-AOC, GSH-Px, and SOD of serum increased in MCE-supplemented piglets ( Chen et al., 2019 ). GSH-Px is an important peroxidase that is widely present in the body, which catalyzes the reduction reaction of lipid peroxides caused by reduced glutathione to protect the cell membrane ( Johnson et al., 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…In order to assess the antioxidant capacity of MCE, several antioxidant parameters such as T-AOC, SOD, GSH-Px, and MDA in serum were monitored. It has been reported that the T-AOC, GSH-Px, and SOD of serum increased in MCE-supplemented piglets ( Chen et al., 2019 ). GSH-Px is an important peroxidase that is widely present in the body, which catalyzes the reduction reaction of lipid peroxides caused by reduced glutathione to protect the cell membrane ( Johnson et al., 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…cordata have antimicrobial and anti-inflammatory activities [ 8 ], it can potentially be used as a growth promoter. In fact, many previous studies have demonstrated the growth-stimulating effect of IQs in a variety of animal species including pigs [ 14 ], chickens [ 15 18 ], and fishes [ 19 – 21 ]. In line with these studies, our results revealed growth-enhancing effects of the four IQ-supplemented diets.…”
Section: Discussionmentioning
confidence: 99%
“…The potential health-promoting properties of IQ from M. cordata have been demonstrated in many animal species, including pigs [14], chickens [15][16][17][18], and fish [19][20][21][22]. These effects include growth performance enhancement, increased appetite, immunostimulation, alteration of the gut microbiome, and increased resistance to bacterial infection.…”
Section: Introductionmentioning
confidence: 99%
“…The IQA formulation used is derived from Macleaya cordata , otherwise known as “plume poppy”, and is rich in IQA’s such as sanguinarine [ 21 ]. Extracts of Macleaya cordata have been shown to improve GIT health, as demonstrated by lowering diarrhea scores and Salmonella populations whilst promoting mucosal growth [ 17 , 20 , 32 ]. In a separate experiment, Macleaya cordata extracts reduced Salmonella , increased Lactobacillus populations, antioxidant capacity, parameters of immune function, small intestinal villus height, and growth performance [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Isoquinoline alkaloids inhibit cellular Na + /K + ATPases, which are important contributors to thermogenesis [ 18 , 19 ] and therefore may provide an approach to mitigate heat stress. Additionally, isoquinoline alkaloids have antioxidant [ 20 ] and anti-inflammatory properties [ 20 , 21 ] which may counteract oxidative stress, inflammation, and disruption of the GIT mucosa prevalent during HS. Thus, this experiment aimed to investigate whether the supplementation of isoquinoline alkaloids and betaine could ameliorate thermoregulatory responses and protect the intestinal integrity of grower pigs experiencing HS.…”
Section: Introductionmentioning
confidence: 99%